2020
DOI: 10.1186/s12909-020-1932-0
|View full text |Cite
|
Sign up to set email alerts
|

Identity matters - perceptions of inter-professional feedback in the context of workplace-based assessment in Diabetology training: a qualitative study

Abstract: Background: Inter-professional collaboration is acknowledged as essential for quality patient-care. However, little is known about receptiveness to inter-professional feedback in the postgraduate training. This study explores, in light of social identity theory, the perceptions of residents, supervising physicians and allied health care professionals regarding inter-professional feedback in the context of workplace-based assessment. Methods: For 6 months, residents in Diabetology at the University Hospital of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…As this stands, it is critical that both supervisors and trainees using WBAs share an understanding of the workflow and purpose of these tools. Given that WBAs have begun to serve a dual purpose (formative or for‐learning versus summative or of‐learning ), 11 there remains an understandable lack of clarity of purpose from the perspective of both trainees and supervisors 7–9,49,50,56,57 . The diversity of understanding regarding the purpose of WBAs has been shown to go beyond the perception of the dual ‘summative versus formative’ purpose.…”
Section: Resultsmentioning
confidence: 99%
“…As this stands, it is critical that both supervisors and trainees using WBAs share an understanding of the workflow and purpose of these tools. Given that WBAs have begun to serve a dual purpose (formative or for‐learning versus summative or of‐learning ), 11 there remains an understandable lack of clarity of purpose from the perspective of both trainees and supervisors 7–9,49,50,56,57 . The diversity of understanding regarding the purpose of WBAs has been shown to go beyond the perception of the dual ‘summative versus formative’ purpose.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, residents were found to actively contemplate the feedback they received based on their judgments of the feedback provider’s clinical credibility and their relationship with that feedback provider [ 24 ]. Similarly, another article found that identity and hierarchy is a significant theme in the feedback process, with social identities being the source of these interprofessional hierarchies [ 25 ]. In that article, residents valued interprofessional feedback and had a positive attitude toward it.…”
Section: Resultsmentioning
confidence: 99%
“… The sampling strategy, a limited number of participants and a focus on psychiatry residents may have affected the validity of the results. Feller and Berendonk [ 25 ] 2020 Switzerland The objective was to explore the perspectives of interprofessional feedback in the context of workplace-based assessment. 7 residents, 7 supervising physicians, and 9 allied healthcare professionals (4 diabetes nurses, 3 nutritionists and 2 psychologists) The study used a qualitative approach based on grounded theory.…”
Section: Table A1mentioning
confidence: 99%
“…In spite of widespread research into professional identity (Burford et al, 2014;Feller & Berendonk, 2020;Fitzgerald, 2020;Goldie, 2012;Kwakman & Schilder, 2005;Monrouxe & Rees, 2017;Rees & Monrouxe, 2018;Ruijters, 2015), the multilayered and multidiscoursal nature of the subject makes it difficult to define professional identity in a straightforward way. According to Beijaard et al (2004), Trede et al (2012), andFitzgerald (2020), a clear definition of professional identity is missing because of the multi-discoursal nature of the subject.…”
Section: Professional Identitymentioning
confidence: 99%